2023
DOI: 10.1002/pol.20230058
|View full text |Cite
|
Sign up to set email alerts
|

Phenylboronic acid‐functionalized glycogens as dynamic nano‐frameworks for conjugation and activation of carbonic anhydrase

Abstract: Biocatalysis is playing an increasingly important role for chemical, pharmaceutical, and food industries, owing to its high efficiency, selectivity and environment‐friendliness. However, it remains challenging to improve the catalytic activity of enzymes since the most frequently used strategies are costly and time‐consuming. In the current study, a new type of glycogen‐based dynamic nano‐frameworks is prepared as additives for the direct activation of carbonic anhydrase (bovine erythrocytes [bCA]). The boroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The authors observed tumour targeting and tumour suppression in vivo in HeLa tumour bearing mice. A separate enzymatic system has been reported by Zhang, et al , 35 that involved functionalising glycogen with phenylboronic acid motifs after sodium meta periodate-mediated oxidation, which then allowed for coupling to the enzyme carbonic anhydrase. Such functional hybrids may have interesting applications on a variety of fronts.…”
Section: Introductionmentioning
confidence: 99%
“…The authors observed tumour targeting and tumour suppression in vivo in HeLa tumour bearing mice. A separate enzymatic system has been reported by Zhang, et al , 35 that involved functionalising glycogen with phenylboronic acid motifs after sodium meta periodate-mediated oxidation, which then allowed for coupling to the enzyme carbonic anhydrase. Such functional hybrids may have interesting applications on a variety of fronts.…”
Section: Introductionmentioning
confidence: 99%